#TITLE_ALTERNATIVE# - WAHYUNI (NIM : 10108049); Pembimbing : Prof. Dr. Roberd Saragih, WINDI
This final project concerned with the determination of optimal investment portfolio by considering consumption. An investor who invest his/her wealth wants the maximum benefit from these investments. The maximum benefit is not easily obtained, if he/she only invests his/her wealth without risk and return calculations. There are two types of investment, namely investment in risky assets and investment in risk-free assets. Investor should combine these two types of investment to get a maximum benefit. In this final project, an investment model will be determined if the investor wants to share his/her wealth to be invested in risky assets and risk-free assets investment by using stochastic differential equations as well as investor uses his/her money for consumption and how much the proportion of investor wealth is used for investment and the amount of consumption are used by investor with stochastic optimal control. To show that the proportion and the amount of consumption giving a maximum benefit, we make simulations by using Matlab software.